2012
DOI: 10.5152/tpd.2012.12
|View full text |Cite
|
Sign up to set email alerts
|

Incidentally Diagnosed Liver and Right Iliac Muscle Hydatid Disease

Abstract: ÖZETEkinokok vücutta tüm organları tutabilir. Karaciğer ve akciğer dışında birlikte veya izole primer başka organ tutulumları da nadir görülmek-tedir. Bu yazıda, solunum problemleri nedeni ile başvuran ve karaciğer hidatik kisti ile iliak kas hidatik kisti tanısı alan 20 yaşında bir erkek hastayı sunuyoruz. Özellikle endemik bölgelerde, karaciğerde kist hidatik tespit edilmiş hastaların mutlaka sistemik incelemeleri yapılmalı ve diğer organlarda bir tutulum olup olmadığı araştırılmalıdır. (Turkiye Parazitol De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…Yoshida et al 21 described a case of intramuscular tumour incidentally detected on positron emission tomography. In addition, there were cases of different muscle parasitic diseases, which were also incidentally identified on CT. 22,23 In conclusion, the present study showed that CT can detect different incidental disorders within the skeletal musculature. Most of them were benign.…”
Section: Discussionsupporting
confidence: 53%
“…Yoshida et al 21 described a case of intramuscular tumour incidentally detected on positron emission tomography. In addition, there were cases of different muscle parasitic diseases, which were also incidentally identified on CT. 22,23 In conclusion, the present study showed that CT can detect different incidental disorders within the skeletal musculature. Most of them were benign.…”
Section: Discussionsupporting
confidence: 53%
“…If total excision cannot be performed during surgery, cyst drainage, removal of the membrane, and irrigation with hypertonic solution of the pouch are required (9). It has been reported in the literature that applying a protoscolicidal agent such as hypertonic saline into the cyst is useful to prevent recurrence and contamination due to a rupture that may occur during surgery (10). We also completely excised the cyst surgically by scraping it from the surrounding tissue.…”
Section: Discussionmentioning
confidence: 99%